Research for the Sustainable Development of Tidal Power in Maine - Johnson, Teresa; Zydlewski, Gayle (Maine Policy Review, 2012)
Generating electricity from Maine’s substantial tides has been a dream for generations. Today, the state is poised for a new era in sustainable tidal-power development. A pilot project is already underway in the Cobscook Bay/Western Passage area near Eastport and Lubec. Tidal-power development presents technical, environmental, and social challenges, however, and the authors discuss how the Maine Tidal Power Initiative is working to develop a cooperative framework that integrates stakeholders, developers, and policymakers to tackle some of these challenges.